Clinical and endoscopic characteristics of post-colonoscopy colorectal cancers detected within 10 years after a previous negative examination - Kodama, Kenta; Kudo, Shin-ei; Miyachi, Hideyuki; Wakamura, Kunihiko; Maeda, Yasuharu; Ichimasa, Katsuro; Ogawa, Yushi; Kouyama, Yuta; Abe, Masahiro; Ogura, Yohei; Okumura, Taishi; Mochizuki, Kenichi; Minegishi, Yosuke; Ishiyama, Misaki; Mori, Yuichi; Misawa, Masashi; Kudo, Toyoki; Hayashi, Takemasa; Ishida, Fumio; Watanabe, Daisuke (Endoscopy International Open, 2021)
Background and study aims We sometimes encounter colorectal cancer (CRC) that is discovered during the time interval between initial colonoscopy and the recommended follow-up examination. Although several studies reported such cases of CRC, most were based on registry data, which implied that the endoscopic quality was not consistent or guaranteed. We aimed to clarify these clinical and endoscopic characteristics at our high-volume center where a retrospective survey could be precisely performed.Patients and methods We retrospectively analyzed patients with CRC who underwent endoscopic resection or surgery from April 2002 to December 2010, categorizing them into two groups: a “study group” of patients with a negative colonoscopy during the previous 10 years, and a “control group” of patients without a previous colonoscopy or with a previous colonoscopy more than 10 years prior.Results A total of 2042 patients had CRC, among which 55 patients were classified into the study group and the remaining 1989 into the control group. The CRC cases in the study group showed a significant association with smaller (< 30 mm) tumor size (odds ratio [OR] 2.3; 95 % confidence interval [CI] 1.3–4.0) and proximal tumor site (OR 1.7; 95 %CI 0.9–2.9). In addition, right-sided and depressed-type T1 CRCs were significantly more common in the study group.Conclusions Tumor size and location were associated with CRCs detected within 10 years after the negative examination. In addition, depressed-type T1 CRCs were more common. Therefore, we should pay more attention to small, right-sided, or depressed-type tumors in daily colonoscopy.